Analisis Pengenaan Pajak Bumi Dan Bangunan Di Kabupaten Jayapura - Transna Putra Urip; Rachmaeny Indahyani; Dominggus Marey (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2021)
This research generally have aims to analyse People’s Perception abaout impotion poverty tax (PBB P2) in Jayapura Distrik. More specific, the objectives are: (a) Requiretmen, (b) Service and c)Equality, The subjek are : Owner the land and building who is them is tax payer, The method be used to analysis  with make discreptionkualitatif which desain in questioner and finaly the output analysis will be kuantitatif,  The result of analysis is  1). People’s Perception for Requiretment is good with score 79.35; 2) People’s Perception for Service is not enought good with score 65.30; 3). People’s perception for Equality is good with score 72.05. Keywords: Perception, Requiretment, Service, and Equality